Emergency Medical Service (EMS) pada Out-Of Hospital Cardiac Arrest (OHCA) Berbasis Aplikasi Internet - Ismail Fahmi; Tuti Afriani (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2017)
Abstrak Out-of Hospital Cardiac Arrest merupakan keadaan henti jantung yang terjadi diluar rumah sakit, dimana sebagian besar korban mengalami kematian karena response time yang lama, untuk itu diperlukan suatu sistemEmergency Medical Service yang baik. Pengembangan Emergency Medical Service berbasis aplikasi internet merupakan salah satu solusi untuk meningkatkan response time penolong maupun ambulans gawat darurat dalam memberikan bantuan. Penulisan ini bertujuan untuk mengetahui bagaimana sistem layanan emergency medical system berbasis aplikasi internet ini digunakan dan seberapa besar manfaat layanan ini bagi pasien dengan Out-of Hospital Cardiac Arrest melalui pendekatan studi literature. Simpulan: layanan emergency medical system berbasis aplikasi internet dengan mobile web service sangat efektif diterapkan dalam pada kondisi henti jantung dan kecelakaan di prehospital. Rekomendasi : perlunya pengembangan layanan emergency yang melibatkan lintas sektoral seperti pemadam kebakaran, kepolisian maupun Badan Sar Nasional Abstrack Emergency Medical Service (EMS) at Out-Of Cardiac Arrest Hospital (OHCA) Based Internet Applications Out-of Hospital Cardiac Arrest is a condition when heart stops beating while patient have not arrived in hospital, where mostly it leads to death because of no immediate response time is given, thus for an Emergency Medical Service system is needed to take care of the patients carefully. The development of internet aplication-based Emergency Medical Service is one of the best solutions, not only to improve response time, but also help patients to get the ambulance immidiately. Based on literature study approach, this paper is aimed on how the internet aplication-based emergency medical system can be used and how it will affect patients with Out-of Hospital Cardiac Arrest. Conclution: internet aplication-based emergency medical service system with mobile web service is critically needed to take care of immediate response of cardiac arrest and accident situation in prehospital condition. Recomendation: the urgency of emergency medical service development which will involve inter-sectoral agency such as fire fighter, police, and National Sar Agent.